2021
DOI: 10.1002/anie.202016220
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of α‐Aryl‐β2‐Amino‐Esters by Cooperative Isothiourea and Brønsted Acid Catalysis

Abstract: The synthesis of α‐aryl‐β2‐amino esters through enantioselective aminomethylation of an arylacetic acid ester in high yields and enantioselectivity via cooperative isothiourea and Brønsted acid catalysis is demonstrated. The scope and limitations of this process are explored (25 examples, up to 94 % yield and 96:4 er), with applications to the synthesis of (S)‐Venlafaxine⋅HCl and (S)‐Nakinadine B. Mechanistic studies are consistent with a C(1)‐ammonium enolate pathway being followed rather than an alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 128 publications
1
8
0
Order By: Relevance
“…Theabsolute configuration of (S)-13 was determined by single crystal X-ray crystallography,w ith all other products assigned by analogy. [29] This stereochemical outcome is consistent with the expected configuration at C(2) if this process proceeds through aC (1)-ammonium enolate intermediate. [19c] Only the introduction of a4 -nitro-substituent led to the product 17 in reduced yield and enantioselectivity.F urther variation of the arylacetic ester showed that incorporation of substituents at both the 3-position (such as 3,4-dimethoxy-, 3-methoxy-and 3-bromo-to give 18-21)and the 2-position (2-methoxy-and 2-bromo-to give 22-23)gave products with consistently high yields and er.…”
Section: Scope Limitations and Synthetic Applicationssupporting
confidence: 75%
“…Theabsolute configuration of (S)-13 was determined by single crystal X-ray crystallography,w ith all other products assigned by analogy. [29] This stereochemical outcome is consistent with the expected configuration at C(2) if this process proceeds through aC (1)-ammonium enolate intermediate. [19c] Only the introduction of a4 -nitro-substituent led to the product 17 in reduced yield and enantioselectivity.F urther variation of the arylacetic ester showed that incorporation of substituents at both the 3-position (such as 3,4-dimethoxy-, 3-methoxy-and 3-bromo-to give 18-21)and the 2-position (2-methoxy-and 2-bromo-to give 22-23)gave products with consistently high yields and er.…”
Section: Scope Limitations and Synthetic Applicationssupporting
confidence: 75%
“…Finally, regeneration of catalyst 6, and concurrent release of product 37, is proposed to be facilitated by para-nitrophenoxide 86,87]. Although not essential for reactivity, the addition of Et 3 N as an auxiliary base may be beneficial as a proton shuttle, and to maintain the isothiourea catalyst in its non-protonated form 6 [77,86]. The enantioselectivity of the transformation indicates the C-C bond forming event takes place on the Si-face of the ammonium enolate.…”
Section: Proposed Mechanismmentioning
confidence: 99%
“…The enantioselectivity of the transformation indicates the C-C bond forming event takes place on the Si-face of the ammonium enolate. This selectivity can be rationalized through preferential formation of the (Z)-ammonium enolate [76][77][78][79]85], which is conformationally-restricted by an intramolecular 1,5-O• • • S interaction [61,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104] and results in the phenyl stereodirecting group of the catalyst blocking the enolate Re-face. The observed poor diastereoselectivity can be tentatively rationalized by a simple stereochemical model that assumes a favored, open pre-transition state assembly where steric interactions are minimized about the forming C-C bond.…”
Section: Proposed Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Tertiary amine catalysts can be classified by the catalytic skeleton bearing an sp 3 - N atom or sp 2 - N atom. The catalysts bearing a catalytic sp 3 - N atom mainly include quinuclidine and dimethylalkyl amine, while the catalysts bearing a catalytic sp 2 - N atom include dimethylaminopyridine (DMAP), N -methylimidazole (NMI), amidine, etc. (Figure ).…”
Section: Introductionmentioning
confidence: 99%